PENGARUH PENDAYAGUNAAN ZAKAT PRODUKTIF TERHADAP KESEJAHTERAAN MUSTAHIQ PADA PROGRAM TERNAK BERGULIR BAZNAS KABUPATEN GRESIK - Nafiah, Lailiyatun (El-Qist: Journal of Islamic Economics and Business (JIEB), 2015)
Research entitled "The Effect of Zakat Productive Utilization Against Animal Welfare Program Revolving Mustahik In BAZNAS Gresik" This is a study that aims to identify and analyze the influence of the productive utilization of zakat through a rolling program for the welfare of livestock mustahiq BAZNAS program beneficiaries in Gresik. This research is quantitative research with survey method. Where the techniques of data collection is done by distributing questionnaires, interviews and documentation. The number of samples in this study were 34 respondents, the sample used is a sample of the population. The analytical method used is a simple linear regression analysis. While testing the hypothesis statistical test is performed with the t test. From the results of statistical tests (t test) found that the value of variable significance productive utilization of zakat is 0,000 (sign ï€¼ Î±), with a beta value of +0.552, in addition to the value of the t variable productive utilization of zakat is known for 3.746 greater than t table (2.042). The simple regression analysis known that the coefficient of determination (R Square) obtained was 0,305 with a simple linear relationship equation in the can is Y = 8.287 + 0.501 X. This means that the variable productive utilization of zakat positive and significant impact on the welfare mustahiq, with In other words if the productive utilization of zakat improved the welfare mustahiq will also increase. With percentage contribution of variable influence on the welfare of the productive utilization of zakat mustahiq was 30.5%. Furthermore, for amil zakat institutions are expected to maximize utilization of zakat to charity productive utilization patterns, accompanied by the assistance for the provision of direction and monitoring for mustahiq recipients.